Digital Crossroads: Navigating Systemic Impediments to Secured Creditor Asset Realization under Kenya’s Insolvency Act, 2015 - Jane Juma; Charles Ochieng’ Oguk (IJRDO - Journal of Social Science and Humanities Research, 2025)
The effective realization of secured assets is a cornerstone for credit markets and economic stability. Kenya’s Insolvency Act, 2015, aimed to modernize insolvency law by balancing debtor rehabilitation with predictable security realization for creditors. However, a significant gap exists between this legislative ideal and practical implementation, marked by a persistent inclination towards avoiding liquidation and business rescue over creditors’ securities, compounded by specific legal provisions and procedural ambiguities. This discrepancy hinders the efficient and predictable recovery of secured collateral, creating adverse economic and financial consequences such as increased perceived lending risk, reduced credit availability, and higher borrowing costs. Furthermore, the erosion of secured collateral value through protracted insolvency processes undermines the fundamental risk mitigation principle of secured lending. This article identifies and categorizes the key systemic impediments hindering the efficient realization of secured assets by creditors under the Insolvency Act, 2015, in Kenya, drawing on statutory analysis, case law, and research work. By understanding these impediments, the study lays the groundwork for exploring how digital solutions, such as Artificial Intelligence (AI) and data analytics, could potentially mitigate these challenges and enhance the efficiency and predictability of secured asset recovery. The objective is to provide insights for evidence-based recommendations to refine the legislative and regulatory framework.